Influence of hypothyroidism on the postoperative course in elderly patients undergoing cardiac surgery - Kowalczuk-Wieteska, Anetta; Foremny, Jerzy; Herdyńska-Wąs, Mirosława; Kucewicz, Ewa; Zembala, Marian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Thyroid hormones are necessary for normal functioning of the organism. Undiagnosed hypothyroidism in elderly patients may lead to a number of life-threatening complications in the postoperative period. Aim: The aim of the study was to establish whether a complicated postoperative course in elderly patients is related to hypothyroidism. Material and methods : The data of 312 patients  65 years of age who underwent cardiac surgery between 01.01.10 and 31.07.10 with euthyroidism documented before the surgery were analysed. Two groups were selected: group I – patients with postoperative euthyroidism (n = 295), and group II – patients with postoperative hypothyroidism (n = 17). Results: Postoperative complications occurred significantly more often in the group of elderly patients with hypothyroidism in the postoperative period. The most frequently observed complications were pleural effusion (n = 7, 41.2%, p < 0.001), delirium (n = 6, 23.5%, p = 0.04), prolonged respiratory therapy (n = 5, 29.4%, p = 0.041) and cardiac tamponade (n = 4, 23.5%, p < 0.001). Conclusions : Postoperative hypothyroidism increases the risk of postoperative complications in elderly patients. All patients  65 years of age should undergo an assessment of the thyroid hormonal function before and after cardiac surgery.